Neurosensorimotor Reflex Integration, Myofascial Release, & Neuro-Developmental Treatment In Children With Cerebral Palsy Athetoid Diplegi: Case Report - Fitri Kirana, Nadya; Arifia Nuraeni, Wilda; Alviana, Vina; Ana Sayida, Alissa; Noviana Putri, Ari; Kusuma Ningrum, Fadhil (Ann Publisher, 2024)
Cerebral Palsy (CP) is a disorder caused by brain damage that results in impaired motor and intelligence function. The causes of CP can be divided into three parts: prenatal, natal, and postnatal. The causes of the Prenatal period are maternal infections, hypoxia or ischemia, and placental abnormalities. The causes of the Christmas period are Birth Trauma, Birth Asphyxia, and premature birth. The causes of the postnatal period are neonatal infections, head trauma, and ongoing medical conditions. Measurements were carried out by palpating muscle tone and primitive reflexes with blank gross motor ability reflexes of children with GMFM. The therapy administration for 4 times has not significantly affected muscle tone with muscle palpation at T1, T2, T3, T4 with hypertonic results. Pathological primitive reflexes with reflex blanks on T1, T2, T3, T4 with positive results of ATNR, Cross extensors, graps, Neck righting, Body righting, Optical righting, Labiryn Righting. Gross motor ability with GMFM at T1, T2, T3, T4 with a yield of 34.4%